The power output-drop height relationship to determine the optimal dropping intensity and to monitor the training intervention - Di Giminiani, R.; Petricola, S. (The Journal of Strength and Conditioning Research, 2016)
The literature currently lacks in methodological approaches to quantify the drop jump intensity and to control the training intervention. This study aimed to determine the average power output-drop height relationship and to quantify the reliability of this relationship across 2 different training interventions (each 8 weeks in length). The relationships were determined for 52 volunteer sports science students who took part in this study (25 male/27 female participants). The drop jumps from 20 to 60 cm were performed on a resistive platform. The reliability of the power output-drop height relationships was quantified for 29 subjects who were selected from the sample and were assigned to a drop jump, vibration, or control groups. The average power output during the drop jump statistically depends on the gender (F(1,250) = 18.844; p = 0.0001) and drop height (F(4,250) = 7.195; p = 0.0001), whereas the interaction between gender and height did not affect the power output (F(4,250) = 0.458; p = 0.767). Both the drop jump and the vibration groups showed a significant main effect over time (F(3,200) = 40.059, p = 0.0001; and F(3,160) = 11.422, p = 0.0001, respectively). The intrasession and interday reliability ranged from "high" (intraclass correlation coefficient [ICC] > 0.80) to "excellent" (ICC > 0.90) among the various drop heights. This study suggests that an individual drop height that maximizes the power output during a drop jump exists and that the test to select this optimal drop height is repeatable over time. Consequently, the test can monitor the improvement in the power output following different training regimens.